Judge Dread: Music Hall Traditionalist or Postcolonial Hybrid - Stratton, Jon (Routledge, 2014)
Judge Dread (Alex Hughes) had nine top forty hits in the early 1970s. All were banned bythe BBC. Almost all the music press ignored him. Hughes was white and working class; hismost significant idea was to combine naughty remakes of nursery rhymes with ska androck steady backing rhythms. Judge Dread’s singles were a big hit with skinheads. By themid-1970s, when the skinhead subculture had died out, Dread was releasing rudeparodies of songs such as ‘Je t’aime . . . moi non plus’ and ‘Y Viva Espana’. This articleargues that Hughes’ work was founded in music-hall genres but also was influenced by theJamaican rudeness tradition. Hughes can be understood as both a music-halltraditionalist and a postcolonial hybrid. His recordings helped to familiarise Britonswith Jamaican music.